ANALYSIS OF DEMAND FORECASTING FOR TEMPEH PRODUCTS AT INDONESIAN TEMPEH HOUSES USING THE HOLT-WINTERS ADDITIVE METHOD APPROACH - Arief Nurdini; Ardhy lazuardy (Asosiasi Dosen Muda Indonesia, 2023)
Rumah Tempe Indonesia is an MSME engaged in processing soybeans into tempeh products. The production system used is made to stockThis production system can cause problems, including the amount of production that does not match consumer needs, causing a shortage or excess of products which are very inefficient for the company's business continuity. For this reason, a study was carried out to determine the forecast for the demand for GMO Tempe at Indonesian Tempe Houses for the next 12 periods using the Holt-winters method and to determine the accuracy of the forecast made. The method used in this research is the Holt-winter method with the help of Ms. Excel Where. The final result of the research using Holt-winters has a level of forecasting accuracy90.1515344%, which means it is very good at predicting the demand for tempe in the future. Forecasting results in periods 37 to 48 respectively are 13372PCS, 12367PCS, 14196PCS, 12848PCS, 16655PCS, 15965PCS, 18032PCS, 15107PCS, 15132PCS, 17969PCS, 14267PCS, 21498PCS.